Rumination as a Mediator of the Prospective Association Between Victimization and Bullying - Malamut Sarah T.; Salmivalli Christina (My University, 2022)
Although there is evidence of concurrent associations between victimization and bully perpetration, it is still unclear how this relation unfolds over time. This study investigates whether victimization in childhood is a prospective risk factor for bully perpetration in early adolescence, and examines rumination as a socio-cognitive factor that may mediate this association. Participants included 553 third graders (43.2% boys; Mage = 9.85), with follow-up assessments when they were in fourth, seventh, and eighth grade. Results indicated that more frequent victimization in grades 3 and 4 was indirectly associated with bully perpetration in grade 8, through rumination in grade 7 about past victimization experiences in elementary school. This pattern remained regardless of whether the rumination elicited feelings of anger or sadness. Our findings demonstrate one pathway through which frequent victimization can lead to perpetration and underscore the important role of rumination in victims’ subsequent adjustment. Implications for future interventions are discussed.